Cue-Polarized Transport of β-actin mRNA Depends on 3′UTR and Microtubules in Live Growth Cones - Leung, Kin-Mei; Lu, Bo; Wong, Hovy Ho-Wai; Lin, Julie Qiaojin; Turner-Bridger, Benita; Holt, Christine E. (Frontiers in Cellular Neuroscience, 2018)
Guidance cues trigger fast responses in axonal growth cones such as directional turning and collapse that require local protein synthesis. An attractive cue-gradient, such as Netrin-1, triggers de novo synthesis of β-actin localized to the near-side compartment of the growth cone that promotes F-actin assembly and attractive steering. How this precise spatial asymmetry in mRNA translation arises across the small expanse of the growth cone is poorly understood. Pre-localized mRNAs in the vicinity of activated receptors could be selectively translated and/or new mRNAs could be trafficked into the area. Here we have performed live imaging of fluorescent-tagged β-actin mRNA to investigate mRNA trafficking dynamics in Xenopus retinal ganglion cell (RGC) axons and growth cones in response to Netrin-1. A Netrin-1 gradient was found to elicit the transport of β-actin mRNA granules to the near-side of growth cones within a 4-7 min window. This polarized mRNA trafficking depended on the 3’ untranslated region (UTR) since mRNA-3’UTR mutant failed to exhibit cue-induced transport. Global application of Netrin-1 significantly increased the anterograde movement of β-actin mRNA along axons and also promoted microtubule-dependent mRNA excursions from the central domain of the growth cone into in the periphery (filopodia and lamellipodia). Dual channel imaging revealed β-actin mRNA riding behind the microtubule plus-end tracking protein, EB1, in movements along dynamic microtubules into filopodia. The mRNA-EB1 movements were unchanged by a Netrin-1 gradient indicating the dynamic microtubules themselves do not underlie the cue-induced polarity of RNA movement. Finally, fast-moving elongated ‘worm-like’ trains of Cy3-RNA, distinct from mitochondria, were seen transporting RNA along axons in vitro and in vivo suggesting the existence of a novel transport organelle. Overall, the results provide evidence that the axonal trafficking of β-actin mRNA can be regulated by the guidance cue Netrin-1 to transduce the polarity of an extracellular stimulus and that the 3’UTR is essential for this cue-induced regulation.